THE SELF REPAIR IN SPEECH OF HOST AND GUEST IN THE TONIGHT SHOW STARRING JIMMY FALLON - Maharani, Jihan; Mahmud, Murni (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
In communicating, speech errors sometimes can occur to anyone and under any condition however people can correct the speech error by doing self-repair in their utterance. The purpose of this study was to discover the types of self-repair in speech of The Tonight Show Starring Jimmy Fallon's host and guests, along with the factors that cause them to make errors in their speeches. This study employed a descriptive qualitative approach, with data drawn from conversation transcriptions of five episodes of The Tonight Show Starring Jimmy Fallon that had been uploaded on YouTube. To analyze the self-repair, researchers used a psycholinguistics approach. This study analyzed self-repair based on Levelt (1983) and Clark and Clark (1977). The results showed that there were three types of self-repair found in the conversation between the host and guests, namely, interrupting the utterance (IU) 27 times, editing terms (ET) 29 times and correction and its relation to the original utterance (COU) 21 times. The most dominant type of self-repair was editing terms. The results also showed that the factor that causes them to make errors in their speech is cognitive reason, situational anxiety and social circumstances.